Surface Roughness Analysis of 3D Printed Parts Using Response Surface Modeling - Biglete, Emmanuelle R.; Christian E. Manuel, Mark; Dela Cruz, Jennifer C.; Verdadero, Marvin S.; Diesta, John Michael B.; Niko G. Miralpez, Daniel; Javier, Ryan Angelo C.; Ian C. Picato, Jemuel (2020 11th IEEE Control and System Graduate Research Colloquium (ICSGRC), 2020)
This study characterizes the surface roughness analysis of 3D printed parts using response surface modeling with varied parameters of 3D printer. The specimen was a 3D printed hollow rectangular object made using an ABS filament. The surface roughness analysis was done by measuring the Arithmetic Average Height (R a ) and Maximum Height of the profile (R t ) parameters given in 1SO 4287 using Surftest SJ-210. The surface roughness analysis of each specimen is subjected to Box-Behnken design through Analysis of Variance. The statistical analysis was used in determination of the effects and significance of the three variables. This study identified that lowering the layer thickness to 0.2 mm of the material being printed was essential to minimize the cusp height during the layer by layer printing of the extruded material. In this study it was found out that having an optimum temperature of 240 degree Celsius provided a lower surface roughness. The optimum printing speed was 60 mm/s, having a faster printing speed required a hotter extrusion temperature in order to have adequate surface roughness. Having a higher printing speed gave a faster time in printing the specimen, but if the temperature wasn't enough then the quality of the print would suffer.